Unreality : the Metaphysics of Fictional Objects - Crittenden, Charles (Cornell University Press, 2019)
Charles Crittenden here offers an original solution to one of the traditional dilemmas of philosophy-whether there can be any thing not existing, since to say that some thing does not exist seems to presuppose its existence. Drawing on the tools of Wittgensteinian philosophy and speech act theory, Crittenden argues that we can and often do make reference to unreal objects such as fictional characters, though they do not exist in any sense at all.